Suitability Analysis of Habitat and Ecotourism of Olive Ridley Sea Turtle (Lepidochelys olivacea) in Development of Turtle Conservation Strategy at Taman Kili-Kili Beach - Vian Dedi Pratama; Sukandar Sukandar; Marjono Marjono; Andi Kurniawan (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
Taman Kili-Kili Beach is designated as an Essential Ecosystem Area (KEE). 188/39/KPTS/013/2020. According to the Supervisory Community Group (Pokmaswas), in 2011-2020, there was an increase in broodstock as many as 52 turtles, and the eggs saved as many as 3323 eggs. However, since 2013 Pokmaswas data shows a decrease in the population of hawksbill and green turtles in turtle conservation areas, which is thought to be caused by climate change, global warming, and animals. This study aims to analyze environmental baselines, turtle populations, and the value of turtle ecotourism (ecological, economic values) and develop strategies to support turtle conservation at Taman Kili-Kili Beach Trenggalek Regency. The results of the adjustment of nesting habitats and turtle ecotourism, calculation of the Habitat Conformity Index (IKH) of turtle nesting, IKH = 77.77%, which belongs to the category (S1) is very suitable to be used as a conservation area and turtle nesting habitat. While the results of the calculation of the Turtle Ecotourism Conformity Index (IKW), IKW = 84.93%, which is included in the (S1) category, which is very suitable for use a turtle tourism area. The strategy for developing turtle ecotourism is in quadrant II, meaning that it utilizes the strengths possessed in the turtle conservation area by minimizing the threats that it will experience.